GAMBARAN KEJADIAN OBESITAS SENTRAL DI POLRES LIMBOTO KABUPATEN GORONTALO TAHUN 2021 - Maesarah Yasin; Deysi Adam; Mayangsari Kau; Lisa Djafar; Herman Hatta (KOLONI, 2022)
In Indonesia, the Central Obesity Rate has increased from year to 2007 at 18.8% and in 2013 (26.6%) and in 2018 it reached 31.0 %), Based on the proportion of central obesity in the population aged >15 years according to characteristics. The employment of PNS/TNI/Polri/BUMN/BUMD is at a rate of (48.5%) and for the proportion of central obesity at the age of 15 years by province, Gorontalo is at a rate of (36.6%,). is at the number (31.0%) (Riskesdas, 2018). Based on the initial data collection conducted by researchers at the Limoto Police, Gorontalo district, 19 people out of 50 people were centrally obese (38%) and 15 people were pre-obese (30%) and 15 people were normal (30%). By knowing these facts, it will be investigated further about the description of the incidence of central obesity in members of the police who are at the Limboto police station, Gorontalo district. Objective: To determine the factors associated with the incidence of central obesity in the Limmoto Police, Gorontalo Regency. Methods: The type of research used is descriptive analysis. The population of this research is using total sampling with a sample of 302 respondents at the Limboto Police Station. Results: The results showed that there were 20 people with central obesity (6.6%), sufficient energy intake 189 (62%), sufficient carbohydrate intake 242 (80.1%), adequate protein intake 256 (84.8%), adequate fat intake 282 (93.4%), smoking at risk 219 (72.5%). Suggestion: For the Limboto Police Chief, it is hoped that they will pay more attention to health conditions, especially a regular diet. Keywords: Nutritional Intake, Smoking Habits and Central Obesity